PENYIMPANAN DATA OBAT DI PUSKESMAS SATU ULU MENGGUNAKAN MY SQL MENGGUNAKAN PROTOTYPING - Ahmad Dimas Aldian Alfurqon; Tata Sutabri (CV. ADIBA AISHA AMIRA, 2023)
Along with the development of the era from the paper era to the digital era that makes it easier for us to work and carry out daily activities, facilities that can be used by many people for their daily activities or even work, there are still many health offices or community service places that use data collection. . Manually. The downside of manual data collection is that a lot of paper is used, complicated, takes up space, and so on which makes data collection less effective and efficient, now it's easier to use MY SQL as a database, we can store as much data as possible and our MY SQL is simpler will also be connected to PHP so that it can be accessed on the Internet which allows it to be used from anywhere, and at any time. The purpose of this proposal is to create a Data Storage Base Prototyping. For this prototyping, I will use figma software, one of the figmas created is to make the UI prototyping to make it prettier and better